Software as Hermeneutics A Philosophical and Historical Study - Possati, Luca M. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book claims that continental philosophy gives us a new understanding of digital technology, and software in particular; its main thesis being that software is like a text, so it involves a hermeneutic process. A hermeneutic understanding of software allows us to explain those aspects of software that escape a strictly technical definition, such as the relationship with the user, the human being, and the social and cultural transformations that software produces. The starting point of the book is the fracture between living experience and the code. In the first chapter, the author argues that the code is the origin of the digital experience, while remaining hidden, invisible. The second chapter explores how the software can be seen as a text in Ricoeur's sense. Before being an algorithm, code or problem solving, software is an act of interpretation. The third chapter connects software to the history of writing, following Kittler's suggestions. The fourth chapter unifies the two parts of the book, the historical and the theoretical, from a Kantian perspective. The central thesis is that software is a form of reflective judgment, namely, digital reflective judgement. Luca M. Possati is a Researcher in Philosophy at the University of Porto, Portugal. His fields of investigation are Philosophy of Technology and Artificial Intelligence. He is the author of many studies in Phenomenology and the History of Philosophy.
1. Introduction: The Paradoxical Onion -- 2. Software and Lived Experience -- 3. Can We Interpret the Code? A Ricoeurian Perspective on Software -- 4. Software and Writing: A Philosophical and Historical Analysis -- 5. The Digital Reflective Judgment -- 6. Conclusions: Toward a Critical Code Thinking.
Keywords: Technology-Philosophy.; Hermeneutics; Philosophy of Technology; Hermeneutics